Trust and Economic Growth - Sjoerd Beugelsdijk; Henri L.F. de Groot; Anton B.T.M. van Schaik (Tinbergen Institute, 2002)
Economists increasingly pay attention to social capital as an important determinant of macroeconomic growth performance. At the same time, there is discussion regarding the robustness of the results of empirical growth studies. In a seminal paper, Knack and Keefer (1997) assess the effect of trust on growth. This paper analyses the robustness of their results along several dimensions, acknowledging the complexity of therobustness concept. Our findings show that the robustness of the relationship between trust and growth in terms of both the size and the significance of the estimated effect, is highly dependent on the set of conditioning variables. An answer to the question whether there is an economic payoff of trust - and if so, how large this payoff actually is - is therefore difficult to provide on the basis of cross sectional empirical growth studies.
Keywords: C12; Z13; 330; Robustness; Trust; Economic Growth.; Social Capital; Vertrauen; Wirtschaftswachstum; Schätzung; Robustes Verfahren; Welt